Observation of red electroluminescence from an Eu2O3/p+-Si device and improved performance by introducing a Tb2O3 layer. (10th February 2017) - Yin, Xue; Wang, Shenwei; Mu, Guangyao; Wan, Guangmiao; Huang, Miaoling; Yi, Lixin
Abstract: We report red electroluminescence (EL) from an Eu2 O3 / p + -Si device with Eu2 O3 film annealed in oxygen ambient at 700 °C. The red EL is ascribed to the characteristic emissions of Eu 3+ ions in Eu2 O3 film and the luminescence mechanism is discussed in detail. In order to optimize the device performance, Eu2 O3 /Tb2 O3 multiple films were deposited on Si wafer, and the result showed EL intensity of the device was obviously enhanced and the turn-on voltage was reduced to about 10 V. Moreover, intensity ratio I ( 5 D0 – 7 F2 )/ I ( 5 D0 – 7 F1 ) was also significantly increased with the hypersensitive transition 5 D0 – 7 F2 as the most prominent group at about 611 nm. The improved performance was attributed to the added Tb2 O3 film that it can be served as the hole-injection layer to afford extra holes injected into the Eu2 O3 layer.